Effects of sulpiride and ethylene glycol monomethyl ether on endometrial carcinogenicity in Donryu rats. Issue 6 (14th July 2015) - Taketa, Yoshikazu; Inoue, Kaoru; Takahashi, Miwa; Sakamoto, Yohei; Watanabe, Gen; Taya, Kazuyoshi; Yoshida, Midori
Abstract: Sulpiride and ethylene glycol monomethyl ether (EGME) are known ovarian toxicants that stimulate prolactin (PRL) secretion, resulting in hypertrophy of the corpora lutea and increased progesterone (P4) production. The purpose of the present study was to investigate how the PRL stimulatory agents affected uterine carcinogenesis and to clarify the effects of PRL on endometrial adenocarcinoma progression in rats. Ten‐week‐old female Donryu rats were treated once with N ‐ethyl‐ N ′‐nitro‐ N ‐nitrosoguanidine (20 mg kg −1 ), followed by treatment with sulpiride (200 ppm) or EGME (1250 ppm) from 11 weeks of age to 12 months of age. Sulpiride treatment inhibited the incidence of uterine adenocarcinoma and precancerous lesions of atypical endometrial hyperplasia, whereas EGME had no effect on uterine carcinogenesis. Sulpiride markedly prevented the onset of persistent estrus throughout the study period, and EGME delayed and inhibited the onset of persistent estrus. Moreover, sulpiride‐treated animals showed high PRL and P4 serum levels without changes in the levels of estradiol‐17β, low uterine weights and histological luteal cell hypertrophy. EGME did not affect serum PRL and P4 levels. These results suggest that the prolonged low estradiol‐17β to P4 ratio accompanied by persistent estrous cycle abnormalities secondary to the luteal stimulatory effects of PRL may explain the inhibitory effects of sulpiride on uterine carcinogenesis in rats. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Sulpiride and ethylene glycol monomethyl ether (EGME) stimulate prolactin (PRL) secretion. Here, the effects of PRL on endometrial carcinogenicity were evaluated in rats. Sulpiride (200 ppm) inhibited the uterine carcinogenesis whereas EGME (1250 ppm) did not. Sulpiride prevented the onset of persistent estrus and induced high PRL and progesterone (P4) serum levels. These results suggest that disruption of the estrous cycle with a decrease in estradiol‐17β to P4 ratio may explain the inhibitory effects of sulpiride on uterine carcinogenesis.